2019
DOI: 10.3390/ijerph16183267
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Human Health Risk Assessment of Heavy Metal Intake via Vegetable Consumption around Pb/Zn Smelters in Southwest China

Abstract: Vegetable contamination in mining and smelting areas has resulted in high dietary intakes of heavy metals, which pose potential health risks to local residents. In this study, paired soil-vegetable samples were collected around Pb/Zn smelters in Southwest China. Probabilistic risks to local residents via vegetable consumption were evaluated with a Monte Carlo simulation. The mean concentrations of As, Cd, Cu, Pb, and Zn in the soils were 116.76, 3.59, 158.56, 196.96, and 236.74 mg/kg, respectively. About 38.18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 47 publications
6
26
0
Order By: Relevance
“…In this study, As had a higher THQ value than other hazardous heavy metals. A similar report also confirmed that As exposure through vegetable ingestion has significant adverse effects on residents [ 23 ]. Thus, much attention should be paid to As although there is a lack of detailed criteria of chemical form.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In this study, As had a higher THQ value than other hazardous heavy metals. A similar report also confirmed that As exposure through vegetable ingestion has significant adverse effects on residents [ 23 ]. Thus, much attention should be paid to As although there is a lack of detailed criteria of chemical form.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies have reported that elevated concentration of HMs was found near the multiple-metal mining and smelter, e-waste dismantling area, and industrial sites [ 16 , 23 , 45 , 53 ]. In addition, Rahmdel et al [ 17 ] and Mandal et al [ 20 ] reported that higher concentrations of Cu and Pb in leaf vegetables were observed in Iran and India than those in the present study, in which samples were collected near the rural districts of industrial town.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The non-carcinogenic risk of human PTEs is expressed by the hazard quotient ( ), which is the ratio of the daily human exposure dose ( , mg·kg −1 ·d −1 ) to the reference dose ( , mg·kg −1 ·d −1 ) [ 25 ]. The specific calculation formula is as follows …”
Section: Methodsmentioning
confidence: 99%